How ‘just’ is hybrid governance of urban nature-based solutions? - Toxopeus, Helen; Kotsila, Panagiota; Conde, Marta; Katona, Attila; van der Jagt, Alexander P.N.; Polzin, Friedemann (Cities, 2020)
Hybrid (or multi-actor) governance has been identified as a key opportunity for upscaling urban nature-based solutions (referred to as urban NBS), representing a demand-driven and cost-effective realization of urban green infrastructure. However it is unclear how such hybrid governance affects the justice outcomes of urban NBS. Through six in-depth cases of urban NBS we show that hybrid governance can lead to both improvements and deterioration of distributional, procedural and recognition justice, depending on the hybrid governance choices. By exploring the tensions between these justice impacts we formulate three main policy implications for hybrid governance settings: the need for transparent decision-making on the distribution of costs and benefits; safeguarding public control over the urban NBS and the use of scientific expertise in combination with bottom-up consultation procedures to recognize both current and future voices. •We analyse justice implications of hybrid governance of urban nature-based solutions (NBS).•We explore distributional, procedural and recognition justice outcomes using six case studies.•Hybrid governance can lead both to deterioration and improvement of justice outcomes.•We explore these tensions in justice outcomes to formulate three policy recommendations.•1- Transparent decision-making; 2- securing public control and 3- context-sensitive science